19.5.17 Synthesis of Nitriles Using Cross-Coupling Reactions - Rudzinski,D. M.; Leadbeater,N. E. (Knowledge Updates 2012/1, 2012)
The synthesis of aryl and hetaryl nitriles by metal-catalyzed cross-coupling reactions is presented. Attention is focused mainly on key methodologies published in the period 2003–2011. As well as the use of alkali metal cyanide salts as sources of cyanide, the application of the less toxic and increasingly popular potassium hexacyanoferrate(II) is also discussed.
Keywords: Referencework; Science of Synthesis; nitriles; cyanide; cyanation; cross coupling; palladium; nickel; copper; aryl halides; hetaryl halides; aryl trifluoromethanesulfonates; aryl methanesulfonates